Differences in 10 km running performance predicted from O2 pulse in elite and trained runners - Smith, D. J.; Gillivray, M. (2004)
The results demonstrate that 10 km performance was correlated with critical speed which supports previous studies. Thus, performance can easily be predicted from shorter maximal runs. Physiologically, our data demonstrates that a high VO2 max is a fundamental requirement and that 10 km performance occurs at a high percentage of VO2 max. Although we could directly measure cardiac output, we could not demonstrate an association between stroke volume or a-vO2 difference and running performance. We have previously demonstrated a strong relationship between stroke volume and 20 km cycling performance. However, in running, other factors, such as running economy and/or biomechanical ability may play significant roles in determining actual performance. The calculated values of stroke volume and a-vO2 difference were very similar to data reported in the literature, however, differences in body size may have been a confounding factor in demonstrating a difference between groups. Further research is required with a larger sample size.